METHODOLOGICAL RECOMMENDATIONS FOR TEACHING THE BASICS IN ADVANCED CLASSES - Badalboyeva Dilorom daughter of Sobirjon; Koshakov Doniyorbek son of Abdumutal (Galaxy International Interdisciplinary Research Journal, 2024)
This article describes effective methodical methods for teaching the topic of fundamentals in in-depth classes. Ways to use interactive teaching, laboratory work and technologies are shown in the teaching of the subject. The article recommends interactive approaches in explaining the chemical properties, reactions and importance of bases in everyday life. These methods help students to master the subject more deeply and to put their chemical knowledge into practice.